2011
DOI: 10.1016/j.jcin.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel Overcomes High On-Clopidogrel Platelet Reactivity Post-Stenting More Effectively Than High-Dose (150-mg) Clopidogrel

Abstract: In patients with HTPR after PCI, prasugrel is more effective compared with high clopidogrel in reducing platelet reactivity, particularly in CYP2C19*2 carriers. Genotyping guidance might be helpful only in case an increased clopidogrel maintenance dose is considered. (Prasugrel Versus High Dose Clopidogrel in Clopidogrel Resistant Patients Post Percutaneous Coronary Intervention (PCI); NCT01109784).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
78
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 34 publications
4
78
0
7
Order By: Relevance
“…In contrast to most of other trials [21][22][23], we also investigated the antiplatelet effects of both prasugrel loading and maintenance doses in ACS patients exhibiting HTPR on clopidogrel. Due to the unique property of the VASP assay to reflect selectively the inhibition of the P2Y 12 receptor by antiplatelet agents, the VASP assay in contrast to other methods of platelet function monitoring may be applied in ACS patients treated with GP IIb/IIIa inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to most of other trials [21][22][23], we also investigated the antiplatelet effects of both prasugrel loading and maintenance doses in ACS patients exhibiting HTPR on clopidogrel. Due to the unique property of the VASP assay to reflect selectively the inhibition of the P2Y 12 receptor by antiplatelet agents, the VASP assay in contrast to other methods of platelet function monitoring may be applied in ACS patients treated with GP IIb/IIIa inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…This intensified platelet inhibition by prasugrel is believed to account for the reduction of ischemic events when compared with clopidogrel therapy in ACS patients undergoing PCI which was shown in the TRITON-TIMI 38 trial [4]. However, recent studies indicated that the phenomenon of HTPR also refers to subjects treated with prasugrel [20,21]. The prevalence of HTPR defined as the PRI value ≥ 50% measured 6-12 h after the administration of a 60 mg loading dose of prasugrel among 301 ACS patients successfully treated with PCI in a multicenter French study was 25.2% [19].…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis 35 comparing loading doses of 300 or 600 mg of clopidogrel found fewer cardiovascular complications with a higher dose, but a large randomized trial showed no effect on thrombosis-related complications in nonresponders. 36 Some authors suggest a dose-dependent strategy based on genotype 17 or switching to prasugrel, 37 as we did if follow-up PRT inhibition was inadequate.…”
mentioning
confidence: 88%
“…Among clopidogrel‐treated patients with high on‐treatment platelet activity, prasugrel and ticagrelor have been shown to effectively inhibit platelet aggregation,9, 10, 11 but randomized controlled trials switching patients with high on‐clopidogrel platelet reactivity to prasugrel or ticagrelor have failed to show clinical benefit 12, 13, 14, 15, 16. Recurrent ischemic events while receiving clopidogrel therapy may affect physician decision making because of perceived clopidogrel “failure,” although these events may not necessarily reflect inadequate platelet inhibition.…”
mentioning
confidence: 99%